Your life in your hands: the security issues with healthcare apps. Issue 4 (April 2016) - Mansfield-Devine, Steve
Abstract : Mobile applications have crept into every part of our lives. The marketing phrase 'There's an app for that' may seem trite, but it's starting to seem like it's true. But like all software, mobile apps have security issues. And one area where this is particularly worrisome – as Stephen McCarney, VP of marketing at Arxan Technologies explains in this interview – is in the area of healthcare. Mobile applications have crept into every part of our lives. But like all software, mobile apps have security issues. One area where this is particularly worrisome – as Stephen McCarney at Arxan Technologies explains in this interview – is in the area of healthcare. Many healthcare providers are issuing mobile apps to make their services more responsive. But the data they work with is both highly attractive to hackers and also vulnerable to attack.